Incidencia de la participación ciudadana en la deconstrucción del concepto de ciudadanía y su aporte en los procesos de resignificación del rol de género en mujeres veedoras de los Centros de Equidad y Justicia en la ciudad de Quito, durante el año 2017. - Lalama Arévalo, Talia Alejandra (2018)
The present investigation presents the results obtained from the work with a group of women between 30 and 60 years old, who make up the Citizen Watch Group called "Life Free of Violence". The work done with these women, from the perspective of Narrative Psychology, allowed identifying through the narration of their Life Stories, events or lived events that played a key role in deconstructing the concepts of Citizenship and their own gender roles. With the work of this group of women, in themes on prevention of Gender Violence and Social Control, the conceptualisations on the Gender Role were also resignified, thanks to the large amount of knowledge apprehended about their own Rights, which is why they manage to stay on the subject of Gender Violence and start a participation in the political and community sphere, through the Replicas. With a more active community social participation, it also reflects the deconstruction that the concept of citizenship had for these women, according to which women were relegated only to private participation spaces, thus breaking the traditional dominant relations schemes, imposed by a patriarchal society, resulting in the empowerment of these women to the experience of their citizenship in some spaces of public participation.